Dissociating Slow Responses From Slow Responding - Salunkhe, Gayatri; Feige, Bernd; Saville, Christopher W. N.; Stefanou, Maria Elena; Linden, David; Bender, Stephan; Berger, Andrea; Smyrnis, Nikolaos; Biscaldi, Monica; Klein, Christoph (Frontiers in Psychiatry, 2020)
Introduction: Increased Intra-Subject Variability (ISV) of reaction times (RTs) is a candidate endophenotype for Attention Deficit Hyperactivity Disorder (ADHD). Previous work indicates that ISV shares a strong positive relationship with response speed. Yet, patients with ADHD are found to be more variable but typically no slower than controls suggesting that the processes underlying ISV and response speed may be distinct. Methods: This brief report addresses the relationship between RT variability and speed by employing dimensional analyses for differentiated performance measures, with a particular focus on the ex-Gaussian measures, across relevant ADHD studies, and in a sample of young healthy adults (N=70). Results: For both ADHD patients and healthy adults, we found that the classical measures for ISV and response speed, namely, reaction time standard deviation (RTSD) and mean reaction time (MRT), were strongly correlated, thus failing to dissociate. Strikingly however, ex-Gaussian tau (τ) correlated strongly with RTSD but shared only little variance with the Gaussian mean, that is mu (μ). This resulted in a dissociation of slow responses (τ) from response speed or – if given – slow responding (μ). Conclusions: Our results highlight the utility of employing the ex-Gaussian measures to disentangle ISV and speed as unique constructs of RT-performance. These findings are particularly relevant for ADHD research as patients are more variable and make more slow responses but are not overall slower than typical controls.